VALUE OF ENDOTHELIUM DYSFUNCTION AND INFLAMMATORY MARKERS LEVEL FOR PREDICTING RISK ASSESSMENT IN UNFAVORABLE COURSE OF ISCHEMIC HEART DISEASE - Vozniuk, L.A.; Doroshkevych, I.O.; Klekоt, O.O.; Kyrychenko, O.V. (World of Medicine and Biology, 2019)
Study of the coronary artery disease course suggests that along with proatherogenic changes in the blood lipid composition in patients with coronary artery disease, an increase in the C-reactive protein (CRP) concentration and proinflammatory cytokines (TNF-α) was observed in comparison with the control group. Characterized by the patterns of the correlations existing between the degree of increase in the level of CRP and ESR, particularly in patients with ACS (r = 0.48, p
Keywords: coronary heart disease; proinflammatory cytokines; PSA; von Willebrand factor; cholesterol